Investigation of Bioabsorbable Screw Usage for Long Bone Fracture Repair in the Horse: Interfragmentary Compression and Axial Load Response in Equine Cadaver Longbone Fractures - Field, J. R.; Hearn, T. C.; Arighi, M. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
The purpose of the study was to compare biomechanical features of bioabsorbable, self-reinforced poly-L-lactic acid (SR-PLLA) and stainless steel (ASIF) 4.5 mm cortical screws. Tests were conducted in equine cadaver third metacarpal bones in which a simulated complete and displaced condylar fracture had been created by osteotomy.An evaluation of the amount of interfragmental compression achieved with each screw type was performed using electrical resistance strain gauges placed in proximity to the osteotomy. This revealed a substantial increase in interfragmental compression when ASIF screws were used compared to the SR-PLLA screw. A hybrid of the two screw types did however achieve adequate interfragmental compression. Comparison of the strength of fracture fixation through response to axial loading revealed significant difference between use of three ASIF screws and a hybrid of one SR-PLLA and two ASIF screws (p = 0.04) or two ASIF (p = 0.01) screws alone. It appeared that the hybrid configuration did have a mechanical advantage over the two ASIF screw arrangement.The results indicate that the SR-PLLA screw is inferior to the stainless steel screw as a means of primary fracture reduction in the horse. A less mechanically demanding role may yet enable usage of the bioabsorbable screws in equine fracture repair, although they proved inadequate in this testing environment.This study examined the inter-fragmental compression and response to axial loading of bioabsorbable and stainless steel 4.5 mm cortical screws in simulated condylar fractures in equine cadaver longbones. The stainless steel screw was superior in both compression and response to axial loading. It was concluded that the bioabsorbable screw did not possess characteristics that would allow it to bring about adequate primary fracture repair.
Keywords: Bioabsorbable; interfragmental compression; fixation strength